2001
DOI: 10.1053/jhep.2001.27093
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of vascular endothelial growth factor in peritoneal macrophages of cirrhotic patients with spontaneous bacterial peritonitis

Abstract: Spontaneous bacterial peritonitis (SBP) is a common complication of cirrhotic patients with ascites that usually results in renal failure and death despite the efficacy of the current antibiotic therapy. The pathogenesis of these phenomena is poorly known but it has been related to the production of vasoactive cell mediators locally acting on the splanchnic vasculature. Because previous studies showed that peritoneal macrophages of cirrhotic patients may produce high quantities of vascular endothelial growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…The expression of VEGF receptor-2 (VEGFR-2) and the endothelial cell marker CD31 [38] is also increased in the splanchnic territory in experimental models of portal hypertension [36,37]. These and other studies provided evidence of increased VEGF-driven splanchnic angiogenesis in portal hypertensive animals and in cirrhotic patients [39][40][41][42].…”
Section: Increased Angiogenesis In Portal Hypertensionmentioning
confidence: 72%
“…The expression of VEGF receptor-2 (VEGFR-2) and the endothelial cell marker CD31 [38] is also increased in the splanchnic territory in experimental models of portal hypertension [36,37]. These and other studies provided evidence of increased VEGF-driven splanchnic angiogenesis in portal hypertensive animals and in cirrhotic patients [39][40][41][42].…”
Section: Increased Angiogenesis In Portal Hypertensionmentioning
confidence: 72%
“…The different behavior of peritoneal macrophages as compared with circulating monocytes already has been observed in previous investigations, and has been considered as indirect evidence that macrophages found in the peritoneum are derived from the milky spots of the omentum, rather than from circulating peripheral monocytes. 9,27 To further characterize hypoxia-induced increases of VEGF and ADM in peritoneal macrophages, time-course experiments assessing protein concentration and messenger expression of both substances were performed. Although hypoxia previously has been shown to induce VEGF and ADM gene transcript in endothelial and smooth muscle cells, tumor-derived cell lines, and murine macrophages, 24,[28][29][30][31] it is not known whether low O 2 tension also induces ADM and VEGF in human peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…6 In this regard, we have shown recently that peritoneal macrophages of cirrhotic patients may produce important amounts of vasodilator/ vasopermeabilizing agents under proper in vitro stimuli or in determined pathologic circumstances. [7][8][9] In the present study we considered the hypothesis that focal areas of low oxygen tension could be an additional stimulus for the production of vasoactive substances by resident macrophages of patients with advanced liver disease. Thus, we assessed whether hypoxia may induce the secretion of vasoactive factors in peritoneal macrophages of patients with cirrhosis and ascites.…”
mentioning
confidence: 99%
“…Previous studies found evidence of increased angiogenesis in the splanchnic territory of portal hypertensive rats and cirrhotic patients (12)(13)(14)(15). Recently, our group was able to show in vivo an increased angiogenesis in the mesenteric microcirculation of rats with PHT, both with and without cirrhosis (Figure 1) (16).…”
Section: Role Of Splanchnic Neoangiogenesismentioning
confidence: 59%